Detailed phenotyping reveals diverse and highly skewed neutrophil subsets in both the blood and airways during active tuberculosis infection - Nhamoyebonde, Shepherd; Chambers, Mark; Ndlovu, Lerato; Karim, Farina; Mazibuko, Matilda; Mhlane, Zoey; Madziwa, Lindiwe; Moosa, Yunus; Moodley, Sashen; Hoque, Monjurul; Leslie, Alasdair (Frontiers in Immunology, 2024)
Neutrophils play a complex and important role in the immunopathology of TB. Data suggest they are protective during early infection but become a main driver of immunopathology if infection progresses to active disease. Neutrophils are now recognized to exist in functionally diverse states, but little work has been done on how neutrophils states or subsets are skewed in TB disease. To address this, we carried comprehensive phenotyping of neutrophils in the blood and airways of individuals with active pulmonary TB with and without HIV co-infection. We found active TB was associated with profound skewing of neutrophils in the blood toward phenotypes associated with activation and apoptosis, reduced phagocytosis, reverse transmigration and immune regulation. This skewing was also apparent in airway neutrophils, with a notable increase in regulatory subsets expressing PDL-1 and LOX-1, which may to contribute to immunopathology. HIV co-infection did not impact neutrophil subsets in the blood but was associated with phenotypic change in the airways and a reduction in key neutrophil functional proteins cathelicidin and arginase 1.